2023
DOI: 10.5935/0004-2749.20230057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strip meniscometry and Schirmer tear test results and tear film breakup time between healthy dogs and dogs with dry eye disease

Abstract: To compare strip meniscometry and Schirmer tear test 1 results and tear film breakup time between dogs with normal eyes and dogs diagnosed with keratoconjunctivitis sicca. Methods: One-hundred fifty-six eyes of 78 dogs, 88 normal eyes, and 68 eyes diagnosed with keratoconjunctivitis sicca were included in the study. The tests were performed in the following sequence: Schirmer tear test 1 was used to allocate the dogs to the normal or keratoconjunctivitis sicca group, followed by the strip meniscometry test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…When correlated, STT-1 and I-Tear test showed a moderate and not signi cant correlation only for dogs with severe dry eye, while the correlation was weak in the other groups. Previous studies have shown a strong correlation between STT-1 and I-Tear test in dogs with KCS (Miyasaka et al 2019;Nascimento et al 2022). This correlation is stronger with increasing severity of tear de ciency.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…When correlated, STT-1 and I-Tear test showed a moderate and not signi cant correlation only for dogs with severe dry eye, while the correlation was weak in the other groups. Previous studies have shown a strong correlation between STT-1 and I-Tear test in dogs with KCS (Miyasaka et al 2019;Nascimento et al 2022). This correlation is stronger with increasing severity of tear de ciency.…”
mentioning
confidence: 84%
“…Dry eye disease (DED) is a complex ophthalmic disorder with multiple underlying causes that result in the loss of the tear lm stability, leading to ocular surface irritation and in ammation (de Oliveira et al 2019). DED can be categorized into two types: one characterized by inadequate production of the aqueous layer of the tear lm, termed quantitative de ciency, and another marked by excessive tear evaporation, known as qualitative de ciency, resulting from insu cient production of lipids or mucin (Berdoulay et al 2005;Nascimento et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the quality of the tears, it is clinically important to determine the quantity of tears present in a patient presumed to have dry eye disease to determine which subtype is/are present. There are a myriad of diagnostic tests available to quantitate aqueous tear production, including STT, endodontic paper point tests, 56 phenol red thread test, 61,81 strip meniscometry test, [82][83][84] and many others. For the purposes of this review, we will compare and contrast the STT-1, the most commonly performed measurement of aqueous tear production.…”
Section: Tear Film Quantity Assessmentmentioning
confidence: 99%
“…As such, SMT is a less invasive tool for the measurement of eyes in clinical practice 70 . SMT values vary from 7.3 ± 2.2 to 10.97 ± 2.93 mm/5 s in healthy canines 5,70,72–74 …”
Section: Measurement Of Tear Productionmentioning
confidence: 99%